الاتصـــال كأداة لرتسيــخ مبادئ المسؤولية الاجتماعيـة في المؤسسة دراسة ميدانية في المركز النفسي البيداغوجي للأطفال المعاقين ذهنيا – سوق اهراس - قمداني سلمى; حازم عليدة (My University, 2021)
Study abstract : • This thesis aimed at studying the impact of communication and the role of instilling the principles of social responsibility on a sample of social institutions, the pedagogical and psychological center for mentally disabled children. • This is in the context of addressing an important problem centered on evaluating the extent to which social institutions practice social responsibility programs and the role played by communication in consolidating these programs. • Where the study, in its theoretical aspect, exposed the concept of social responsibility, which is a new concept that means the institution's consideration of social concerns when performing its social activity, as well as the concept of institutional communication, which is based on the exchange of information within the organization through external and internal communications. In this context, this study came to identify the role played by communication Institutionalization in consolidating the principles of social responsibility in the Psychological Pedagogical Center for Mentally Handicapped Children - Souk Ahras State - by asking the following central question: What is the role of communication in consolidating the principles of social responsibility in the pedagogical psychological center for mentally handicapped children - Souk Ahras -? Sub-questions emerged from it: • What is the reality of the internal communication in the pedagogical and psychological center for mentally handicapped children? • What is the commitment of the Psycho-pedagogical Center for mentally handicapped children to respect the basic rights of the child? • What are the most prominent goals and objectives of the pedagogical psychological center in applying the pillars of social responsibility? • As for the method adopted in this study, it is the "descriptive method". We used the questionnaire as a main tool in the study to collect data in the field, as we distributed it to an intentional sample of 19 pedagogues, in addition to adopting observation and interview as a supporting tool for the questionnaire and as secondary tools to reach more accurate information. As for the practical side, a set of results have been reached as follows: • Communication in the institution is based on building friendly relations between the pedagogue and the mentally handicapped child. • Formal communication (ascending) is the most frequented in the pedagogical center for mentally handicapped children. The center provides the appropriate atmosphere for the mentally disabled child inside and outside the center by ensuring the necessity of moral behavior, good dealing and providing social and exploratory control within the family environment. • The center aims to achieve the independence of the mentally disabled child and build his personality and the ability to adapt and belong. ---------------------------------- ملخص الدراسة: • هدفت هذه الرسالة إلى دراسة أثر التواصل ودوره في ترسيخ مبادئ المسؤولية الاجتماعية لدى عينة من المؤسسات الاجتماعية، وهي المركز التربوي والنفسي للأطفال ذوي الإعاقة الذهنية. • يأتي ذلك في إطار معالجة إشكالية مهمة تتمحور حول تقييم مدى ممارسة المؤسسات الاجتماعية لبرامج المسؤولية الاجتماعية، ودور التواصل في ترسيخها. • حيث تناولت الدراسة في جانبها النظري مفهوم المسؤولية الاجتماعية، وهو مفهوم حديث يعني مراعاة المؤسسة للقضايا الاجتماعية عند ممارسة نشاطها الاجتماعي، بالإضافة إلى مفهوم التواصل المؤسسي الذي يقوم على تبادل المعلومات داخل المؤسسة من خلال الاتصالات الخارجية والداخلية. في هذا السياق، جاءت هذه الدراسة للتعرف على دور مأسسة التواصل في ترسيخ مبادئ المسؤولية الاجتماعية في المركز النفسي التربوي للأطفال المعاقين ذهنيًا - ولاية سوق أهراس - من خلال طرح السؤال المحوري التالي: ما دور التواصل في ترسيخ مبادئ المسؤولية الاجتماعية في المركز النفسي التربوي للأطفال المعاقين ذهنيًا - ولاية سوق أهراس -؟ ومنبثق عنه أسئلة فرعية: • ما واقع التواصل الداخلي في المركز النفسي التربوي للأطفال المعاقين ذهنيًا؟ • ما مدى التزام المركز النفسي التربوي للأطفال المعاقين ذهنيًا باحترام الحقوق الأساسية للطفل؟ • ما أبرز أهداف وغايات المركز النفسي التربوي في تطبيق أركان المسؤولية الاجتماعية؟ • أما المنهج المتبع في هذه الدراسة فهو "المنهج الوصفي". استخدمنا الاستبيان كأداة رئيسية في الدراسة لجمع البيانات ميدانيًا، حيث وزعناه على عينة قصدية قوامها 19 تربويًا، بالإضافة إلى اعتماد الملاحظة والمقابلة كأداة داعمة للاستبيان، وكأدوات ثانوية للوصول إلى معلومات أكثر دقة. أما في الجانب التطبيقي، فقد توصلنا إلى مجموعة من النتائج، منها: • يعتمد التواصل في المؤسسة على بناء علاقات ودية بين المربي والطفل المعاق ذهنيًا. • يُعد التواصل الرسمي (التصاعدي) الأكثر شيوعًا في المركز التربوي للأطفال المعاقين ذهنيًا. يوفر المركز الأجواء المناسبة للطفل المعاق ذهنيًا داخل المركز وخارجه، من خلال ضمان ضرورة السلوك الأخلاقي وحسن التعامل، وتوفير الرقابة الاجتماعية والاستكشافية ضمن البيئة الأسرية. • يهدف المركز إلى تحقيق استقلالية الطفل المعاق ذهنيًا، وبناء شخصيته، وقدرته على التكيف والانتماء. ------------------------------- Résumé de l'étude : • Cette thèse visait à étudier l'impact de la communication et le rôle d'inculquer les principes de responsabilité sociale sur un échantillon d'institutions sociales, qui est le centre pédagogique et psychologique pour les enfants handicapés mentaux. • Ceci dans le contexte de la résolution d'un problème important centré sur l'évaluation de la mesure dans laquelle les institutions sociales pratiquent les programmes de responsabilité sociale et le rôle joué par la communication dans la consolidation de ces programmes. • Où l'étude, dans son aspect théorique, a exposé le concept de responsabilité sociale, qui est un nouveau concept qui signifie la prise en compte par l'institution des préoccupations sociales dans l'exercice de son activité sociale, ainsi que le concept de communication institutionnelle, qui est basé sur la échange d'informations au sein de l'organisation à travers les communications externes et internes Dans ce contexte, cette étude est venue identifier le rôle joué par l'institutionnalisation de la communication dans la consolidation des principes de responsabilité sociale dans le centre pédagogique et psychologique pour enfants handicapés mentaux - l'état de Souk Ahras - en posant la question centrale suivante : Quel est le rôle de la communication dans la consolidation des principes de responsabilité sociale dans le centre psychologique pédagogique pour enfants handicapés mentaux - Souk Ahras - ? Des sous-questions en sont ressorties : • Quelle est la réalité de la communication interne au centre pédagogique et psychologique pour enfants handicapés mentaux ? • Quel est l'engagement du Centre psychopédagogique pour enfants handicapés mentaux à respecter les droits fondamentaux de l'enfant ? • Quels sont les buts et objectifs les plus importants du centre psychologique pédagogique dans l'application des piliers de la responsabilité sociale ? • Quant à la méthode retenue dans cette étude, il s'agit de la « méthode descriptive ». Nous avons utilisé le questionnaire comme outil principal de l'étude pour collecter des données sur le terrain, car nous l'avons distribué à un échantillon intentionnel de 19 pédagogues, en plus d'adopter l'observation et l'entretien comme outil d'aide au questionnaire et comme outils secondaires pour atteindre informations plus précises. Pour ce qui est du côté pratique, un ensemble de résultats ont été atteints comme suit : • La communication en institution repose sur la construction de relations amicales entre le pédagogue et l'enfant handicapé mental. • La communication formelle (ascendante) est la plus fréquentée dans le centre pédagogique pour enfants handicapés mentaux. Le centre offre une atmosphère appropriée à l'enfant handicapé mental à l'intérieur et à l'extérieur du centre en garantissant la nécessité d'un comportement moral, de bonnes relations et en assurant un contrôle social et exploratoire au sein de l'environnement familial. • Le centre vise à atteindre l'autonomie de l'enfant handicapé mental et à construire sa personnalité et sa capacité d'adaptation et d'appartenance
Keywords: التواصل، المسؤولية الاجتماعية، المؤسسات الاجتماعية